2015
DOI: 10.1017/s1751731115001202
|View full text |Cite
|
Sign up to set email alerts
|

Delayed muscle development in small pig fetuses around birth cannot be rectified by maternal early feed restriction and subsequent overfeeding during gestation

Abstract: Intrauterine variations in nutrient allowance can alter body composition and tissue features of the porcine offspring around birth. This study aimed to determine the effects of fetal weight variations between littermates and of maternal dietary regimen during gestation on fetal muscle traits just before birth. Fourteen pregnant gilts were reared under a conventional (control, CTL; n = 7) or an experimental (treatment, TRT; n = 7) dietary regimen during gestation. The dietary treatment provided 70% of the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Hence, the presence of embryonic MyHC may impair muscle functionality in IUGR pigs. Our results corroborate those reported by Perruchot et al (), which demonstrated a greater amount of the embryonic MyHC isoform in small fetuses, suggesting delayed myofiber development. Thus, IUGR individuals exhibit compromised postnatal growth which may be attributable to skeletal muscle delayed maturity.…”
Section: Discussionsupporting
confidence: 93%
“…Hence, the presence of embryonic MyHC may impair muscle functionality in IUGR pigs. Our results corroborate those reported by Perruchot et al (), which demonstrated a greater amount of the embryonic MyHC isoform in small fetuses, suggesting delayed myofiber development. Thus, IUGR individuals exhibit compromised postnatal growth which may be attributable to skeletal muscle delayed maturity.…”
Section: Discussionsupporting
confidence: 93%
“…Hence, the presence of embryonic MyHC may impair muscle functionality in IUGR pigs. Our results corroborate with those reported by Perruchot and colleagues[20] which demonstrated greater amount of the embryonic MyHC isoform in small fetuses,suggesting delayed myofiber development. The molecular regulation of skeletal muscle postnatal myogenesis in IUGR animals still lack clarification, especially regarding postnatal development.…”
supporting
confidence: 93%
“…Thus, IUGR individuals exhibit compromised postnatal growth [17] [18] which may be due to skeletal muscle damage [19] and delayed skeletal muscle maturity [20].…”
Section: Introductionmentioning
confidence: 99%
“…Foetal myogenesis in IUGR piglets is impaired due to many changes in the mRNA abundance of muscle proteins that are involved in cellular structure, macronutrient metabolism, protein synthesis and degradation, immune response, extracellular matrix and antioxidant function (Wang et al, 2008). The longissimus muscle of small foetuses especially exhibits higher expression levels of DLK1 and NCAM1/CD56 (Perruchot et al, 2015), two genes known to be downregulated during myogenesis in normal littermates. Expression levels of the embryonic MyHC, both at the mRNA and protein levels, are also higher in small foetuses, whereas the ratios of perinatal to embryonic and of adult fast to developmental MyHC isoforms are lower in IUGR foetuses when compared with their medium-weight littermates .…”
Section: Deviation From Normal Tissue Development In Piglets With Intmentioning
confidence: 99%
“…Birth weight of piglets from sows receiving an increased feed supply during gestation is generally not affected, as reviewed in Chapter 1 (Farmer and Edwards, 2020), and there are inconsistent results on the myofibre types and postnatal growth rate of those piglets (Bee 2004;Cerisuelo et al, 2009;Gatford et al, 2003;McNamara et al, 2011;Nissen et al, 2003). Moreover, overfeeding subsequent to a period of early maternal diet deprivation does not modify the expression levels of stem cell markers, myogenic signals and MyHC isoforms in skeletal muscle of piglets just before birth, but upregulates IGF2 expression (Perruchot et al, 2015). Such findings demonstrate that this feeding strategy aiming to induce catch-up growth in later gestation cannot counteract the deleterious effect of IUGR and, in fact, it even tends to reduce piglet birth weight when compared to sows fed adequate diets throughout gestation (Farmer et al, 2014).…”
Section: Overfeeding In Gestationmentioning
confidence: 99%